Perancangan Sistem Monitoring Pegawai Berbasis Android Pada Politeknik Negeri Media Kreatif PSDKU Medan - Andrian Andrian; Efrizal Siregar; Nurianti Sitorus; Reniwati Lubis; Syafriyandi Syafriyandi; Herri Trisna Frianto (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2022)
Employee discipline is one indicator of an institution that has experienced an increase in good personal qualities. There are so many agencies that are developing and have a good image in the eyes of the public not because the products they produce are good but because of the discipline of employees or employees which causes service performance to their customers to increase. As is the case with the PSDKU Medan Creative Media State Polytechnic Campus, it can develop even better only by exercising discipline to its employees, both educational staff and teaching staff (lecturers). So far, employee discipline has only been monitored based on electric attendance provided by the university. But the problem is the existence of these employees in the institution. Very often some employees are not at the location during working hours so that it can reduce service to students or the community. Currently, on Android, there is GPS (Global Positioning System) technology that can provide location information where the user is during work hours. So by developing an Android application, it can access the location of application users which can prevent employees or employees from being in their proper place. This can solve the problems that occur at the PSDKU Medan Creative Media State Polytechnic.Kata kunci:  Monitoring System, Global Positioning System, Employee